A LITERATURE REVIEW: THE POTENTIAL OF NATURAL INGREDIENTS AS ANTIDEPRESSANTS - Ranatri Puruhita; Arifah Sri Wahyuni; Andi Suhendi (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Changes in mood, physical well-being, and behavior, such as sleep and hunger patterns, psychomotor abilities, concentration, anhedonia, exhaustion, hopelessness, helplessness, and suicidal thoughts, define a mental illness known as depression. Alternative therapies that can be used to avoid these side effects include herbal medicines from several types of plants. This literature review aims to determine the potential of natural ingredients that have antidepressant activity in plant biomarkers, methods of obtaining biomarkers, effective dose, and their mechanisms of action. Article searches use keywords (